2015
DOI: 10.1377/hlthaff.2014.1453
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Latin America’s Progress Toward Achieving Universal Health Coverage

Abstract: Two commonly used metrics for assessing progress toward universal health coverage involve assessing citizens' rights to health care and counting the number of people who are in a financial protection scheme that safeguards them from high health care payments. On these metrics most countries in Latin America have already "reached" universal health coverage. Neither metric indicates, however, whether a country has achieved universal health coverage in the now commonly accepted sense of the term: that everyone--i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 16 publications
0
65
0
Order By: Relevance
“…A third indicator, skilled birth attendance, was selected to represent treatment coverage. These three outcomes have been previously used to indicate progress towards UHC and were available in the surveys [10,26,27].…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…A third indicator, skilled birth attendance, was selected to represent treatment coverage. These three outcomes have been previously used to indicate progress towards UHC and were available in the surveys [10,26,27].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…An article by Wagstaff et al published the same year (2015) assessed the progress towards UHC using data from 112 household surveys from 1990 to 2013 for twenty Latin American countries. The overall conclusion was that all countries were progressing well in the right direction towards UHC, but still far from achieving full UHC [10]. Despite Wagstaff et al conclusion, several studies looking at the impact of the health care reforms on different aspects of the equity dimension in countries like Brazil, Mexico and Colombia have however suggested that the implemented reforms did not contribute to improve equity and fairness in the health system and therefore to achieve UHC due internal and external factors such as a huge fragmentation, poor delivery and unsustainable nancing of health system.…”
Section: Introductionmentioning
confidence: 99%
“…22 Monitoring universal health coverage is more complex than monitoring only coverage of reproductive, maternal, newborn and child health care; indicators also need to cover cardiovascular disease, mental health, injuries, cancer and several infectious diseases, as well as financial protection. 23,24 Given that universal health coverage tracer indicators tend to be age-specific, and in some cases sex-specific, it is unlikely that a cumulative index such as co-coverage will be useful as a single summary measure. Thus, the approach of using averages -as in the composite coverage index -is more appropriate for monitoring universal health coverage.…”
Section: ‫ملخص‬mentioning
confidence: 99%
“…The universal health coverage measurement exercises mentioned above [22][23][24] all stress the lack of timely, populationbased and regular information for monitoring coverage. The availability of data on reproductive, maternal, newborn and child health is greater than for other age ranges, particularly due to the increase in DHS and MICS during the MDG era.…”
Section: ‫ملخص‬mentioning
confidence: 99%
“…As different regions and, more critically, nations have different sensitivities about sexual and reproductive health concerns, care must be taken to maintain a holistic perspective 42,43 . As a cautionary example, the emerging global universal health care monitoring effort takes a broad perspective in the diverse areas of reproductive, maternal, neonatal, child and adolescent health 44,45 but care should be taken for family planning, being part of clinical practice, to feature among its set of health interventions as opposed to being grouped elsewhere due to its linkages with other social conditions 46 . National commitment to a common holistic approach will be essential for accountability and programmatic corrections.…”
Section: Operationalisationmentioning
confidence: 99%